DNS blocking in IR: bbc.com, facebook.com, google.com, instagram.com, medium.com +13 more (Iran) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Iran. Data sourced from CensoredPlanet.
Censorship Incident ID: IR-2026-0011. Severity: critical. Confidence: 85%